2012
DOI: 10.1016/j.jcrc.2011.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of lactic acidosis in diabetic ketoacidosis

Abstract: Purpose The prevalence and clinical significance of lactic acidosis in diabetic ketoacidosis (DKA) are understudied. The objective of this study was to determine the prevalence of lactic acidosis in DKA and its association with intensive care unit (ICU) length of stay (LOS) and mortality. Methods Retrospective, observational study of patients with DKA presenting to the emergency department of an urban tertiary care hospital between January 2004 and June 2008. Results Sixty-eight patients with DKA who prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 16 publications
7
80
2
4
Order By: Relevance
“…14 Diabetic ketoacidosis, HHNKS, lactic acidosis and hypoglycemia presented in varying combinations in some patients, similar findings were seen in the study conducted by Cox K et al 15 Diabetic ketoacidosis was commonly associated with lactic acidosis. Hypoglycemia was associated with all other metabolic complications of diabetes mellitus.…”
supporting
confidence: 73%
“…14 Diabetic ketoacidosis, HHNKS, lactic acidosis and hypoglycemia presented in varying combinations in some patients, similar findings were seen in the study conducted by Cox K et al 15 Diabetic ketoacidosis was commonly associated with lactic acidosis. Hypoglycemia was associated with all other metabolic complications of diabetes mellitus.…”
supporting
confidence: 73%
“…More recently, however, it was demonstrated that the metabolic derangements itself present in DKA might contribute as well to the elevated lactate levels 4. Various studies have reported the presence of a positive correlation between glucose levels and ketone (β-hydroxybutyrate) levels on the one hand, and lactate levels on the other hand 4 5.…”
Section: Discussionmentioning
confidence: 99%
“…Levels around 4-5 mmol/l are universally accepted as being elevated. Such serum lactate concentrations in conjunction with a blood pH value of ≤ 7.35 constitute a lactic acidosis (10)(11)(12).…”
Section: Page 5 Of 18mentioning
confidence: 99%